An overview of Malaysian real estate investment trusts' management advisory style - Abdul Jalil, Rohaya (2015)
The establishment of Malaysian real estate investment trusts (M-REITs) through introduction of Malaysian REITs Guideline in 2005 has adopted the REITs practices in counterparts with few modifications that tailor to the local need. However the aspect of M-REITs’ management advisory style has not been mentioned clearly. This study is appraising the M-REITs’ management advisory style by overview the United States (US) REITs experiences. A content analysis of previous literature on US REITs, Malaysian REITs Guidelines and M-REITs’ annual report was conducted to review the practices of M-REITs’ management advisory style. This study reveals that understanding of external, and internal advisory management in Malaysia was different. Malaysian REITs appointed an external advisory manager company which was established by the REITs themselves. The REITs hold a significance amount of share in this external advisory managing company. The role to determine the new acquisition and plan for expansion remained in the REIT firm. This preliminary study is essential to stimulates further attention on M-REITs management advisory style since US literatures suggest advisory influence firm value, debt financing and profit maximization.